1996
DOI: 10.1007/bf02172369
|View full text |Cite
|
Sign up to set email alerts
|

ThehapC gene ofAspergillus nidulans is involved in the expression of CCAAT-containing promoters

Abstract: The 5' regulatory region of the amdS gene of Aspergillus nidulans, which encodes an acetamidase required for growth on acetamide as a carbon and nitrogen source, contains a CCAAT sequence which is required for setting the basal level of amdS expression. Mobility shift studies have identified a factor in A. nidulans nuclear extracts which binds to this CCAAT sequence. In Saccharomyces cerevisiae the HAP3 gene encodes one component of a multisubunit complex that binds CCAAT sequences. A search of the EMBL and Sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 41 publications
7
56
0
Order By: Relevance
“…Subsequently, Kennedy and Turner (32) demonstrated that the expression of acvA, another gene in the PN cluster encoding ␦-(L-␣-aminoadipyl)-L-cysteinyl-D-valine synthetase, is the rate-limiting step in PN biosynthesis. Furthermore, a reduction in ipnA caused by deletion of the hapC gene (which encodes a component of the wide-domain-regulatory CCAAT-binding complex AnCF/AnCP/ PENR1 [28,37,40]) resulted in only a moderate reduction in PN, since acvA expression was only slightly affected by the deletion (37). Our results showed a correlation between acvA expression levels and the bioassay results ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…Subsequently, Kennedy and Turner (32) demonstrated that the expression of acvA, another gene in the PN cluster encoding ␦-(L-␣-aminoadipyl)-L-cysteinyl-D-valine synthetase, is the rate-limiting step in PN biosynthesis. Furthermore, a reduction in ipnA caused by deletion of the hapC gene (which encodes a component of the wide-domain-regulatory CCAAT-binding complex AnCF/AnCP/ PENR1 [28,37,40]) resulted in only a moderate reduction in PN, since acvA expression was only slightly affected by the deletion (37). Our results showed a correlation between acvA expression levels and the bioassay results ( Fig.…”
Section: Discussionmentioning
confidence: 51%
“…PENR1 positively regulates the expression of two penicillin biosynthetic genes, ipnA and aatA. Deletion of hapB, hapC, and hapE genes, which encode PENR1 complex components, resulted in identical phenotypes characterized by low levels of ipnA and aatA expression as well as a slow-growth phenotype and a reduction in conidiation (74,87,112).…”
Section: Ccaat Binding Protein Complexmentioning
confidence: 99%
“…The hapC gene of A. nidulans was identified as a homolog of the HAP3 gene of S. cerevisiae (40). Deletion of this gene resulted in low levels of expression of amdS, aatA, and ipnA reporter gene fusions (28,40).…”
mentioning
confidence: 99%